Eskimo school on the Andreafsky: a study of effective bicultural education - Kleinfeld, Judith (Praeger, 1979)
This is a case study of the St. Mary Catholic boarding school in Alaska which enrols Eskimo adolescents from remote villages that are undergoing rapid cultural change. It produces graduates with the skills needed for access to the opportunities of the majority culture, in particular, the communication skills required for further education. St. Mary's graduates succeed in college much more frequently than comparable Eskimo students. However, the school does not alienate its students from their original background. Students adapt easily to their environment when back in the villages. Administered by the Jesuit order, the school is in large part a creation of the Ursulines who form the faculty. Many of the teachers are young volunteers, often only slightly older than the students. This creates a very intensive interaction among students and teachers. Another special feature of the school is the emphasis on personality and character development. In the curriculum, elements of the local Eskimo culture are harmoniously integrated with the majority culture. Operating under severe financial constraints, the school lacks facilities, equipment and vocational or bilingual programmes. Inspite of these difficulties, the school succeeds in maintaining academic standards and above all, in creating a spirit of co-operation and trust which accounts for the favourable attitudes of the students towards their school